GENERAL PRACTITIONERS KNOWLEDGE REGARDING FUNCTIONAL DYSPEPSIA - Farah Ahmad; Syed Hasan Danish; Ahsan Ashfaq; Sharmeen Naz; Rao Abdul Basit (ziauddin University, 2019)
Background: Most researches on Gastrointestinal (GI) disorders are conducted in secondary health care settings, yet majority patients present at a primary health care level. Functional dyspepsia (Idiopathic or non ulcer dyspepsia) constitutes a tremendous workload in primary care. This study aims to assess the knowledge of general practitioners regarding functional dyspepsia. Methods: Data was collected through a cross sectional study in 2016, targeting 18 towns of Karachi. Multistage sampling technique was employed. A total of n=250 general practitioners were inducted in the study. Data was collected through self administered questionnaire developed from the ROME III guidelines of functional dyspepsia. Descriptive analysis was carried out through SPSS 21. Results: From the total n=250 general practitioners only 17.5% were able to correctly identify the correct definition of functional dyspepsia. Less than 1% knew that ROME III guidelines are being followed for management of functional dyspepsia. The diagnostic criterion for functional dyspepsia was known to only 15% general practitioners. Only two alarm signs were identified by the participants of the study. Conclusion: The average number of patients seen by General Practitioners is high yet their knowledge is weak and practices are not according to the standard guidelines